A Program for Inclusive Education Towards Equitable and Non-Discriminatory Education - Sriwahyuni, Eci; Khermarinah, Khermarinah (Journal of Social Work and Science Education, 2024)
Every human being requires education as a fundamental necessity to pursue their future, yet many marginalized children with special needs still struggle to get the education they need. To start providing equal and non-discriminatory education, the government created legislation governing inclusive education through Ministerial Regulation Number 70 of 2007. Planning, literature search, criteria assessment (inclusion and exclusion), quality assessment, data collection, and data analysis are the six steps of the systematic literature review (SLR) process that are used in this study. The purpose of this study is to identify the goals of inclusive education programs, how they should be implemented in the classroom, and any challenges that may arise. The primary goal of adopting inclusive education programs in schools, according to the results of data analysis, is to give kids with special needs the chance to engage in formal education so they can learn alongside regular students. Before integrating kids with special needs into the inclusive education program, an assessment process is conducted. The standard curriculum is then implemented, with modifications made based on the needs of the students, to facilitate learning. There are still numerous challenges in the way of this inclusive education program’s implementation, such as a lack of infrastructure and resources to facilitate inclusive learning. Lack of training, the scarcity of special assistant teachers for ABK, and the local government’s neglect of program evaluation are the main causes of the teacher shortage.